Building Entrepreneurial Capacity: The Role of Publicly Funded Training Programs in Empowering MSMEs in Dharmasraya, Indonesia - Diapepin, Mukti; Febrina, Donna Ikranova; Sunaryo, Joko; Astika, Yulia Wiji; Elsyra, Nova; Wismar, Teta; Hamirul, Hamirul (Indonesian Community Empowerment Journal, 2024)
Micro, small, and medium enterprises (MSMEs) are vital to the Indonesian economy, especially in rural areas like Dharmasraya. This community service project aimed to empower MSMEs by building their entrepreneurial capacity through publicly funded training programs. Using a participatory action research approach, a needs assessment was conducted with 100 MSME owners in Dharmasraya to identify challenges and training needs. Based on the findings, workshops and mentoring sessions were designed and delivered, focusing on financial literacy, marketing strategies, digital literacy, and business plan development. The training program significantly improved participants' understanding of key business concepts, including financial management, marketing, and digital tools. Participants also showed increased confidence in managing and growing their businesses. The program fostered a sense of community and peer learning among MSME owners. In conclusion, publicly funded training programs are crucial for building entrepreneurial capacity and empowering MSMEs in Dharmasraya. This initiative highlights the effectiveness of participatory approaches in addressing community needs and fostering sustainable economic development.